How Does Having a Good Ear Promote Instructed Second Language Pronunciation Development? Roles of Domain‐General Auditory Processing in Choral Repetition Training. Issue 1 (30th January 2022) - Shao, Yujie; Saito, Kazuya; Tierney, Adam
Abstract: Growing evidence suggests that auditory processing ability may be a crucial determinant of language learning, including adult second language (L2) speech learning. The current study tested 47 Chinese English‐as‐a‐Foreign‐Language students to examine the extent to which two types of auditory processing, i.e., perceptual acuity and audio‐motor integration, related to improvements in the comprehensibility and nativelikeness of L2 speech following two weeks of choral repetition training (i.e., shadowing). All participants' pronunciation proficiency became significantly more comprehensible over time, and the degree of improvement in the nativelikeness of pronunciation was tied to the ability to remember and reproduce sounds (i.e., audio‐motor integration). The findings suggest that robust auditory‐motor integration may play a key role in the acquisition of advanced‐level L2 pronunciation proficiency (i.e., comprehensible and nativelike speech).